2021
DOI: 10.11609/jott.7339.13.11.19500-19508
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the flush response and flight initiation distance of three owl species in the Andaman Islands

Abstract: Effects of anthropogenic pressures on birds of the Andaman Islands have been documented to some extent, however studies on the effect of human activities on the behavioural response of these birds are limited. This study assessed the anti-predatory behaviour (flush response - FR and flight initiation distance - FID) of three owl species (Otus sunia, Otus balli, and Ninox obscura) in response to human stimuli and factors influencing it on the Andaman Islands. In total, 63 % of owls flushed from their roost site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…We could not measure the anti-predatory behaviour of owls in response to non-human predators. However, experimental results showed that flush response and flight initiation distance of roosting owls decreased in response to approaching human stimuli when they roosted in well concealed spiny vegetation (Sureshmarimuthu et al 2021). Our results suggest thus, that on Andaman Islands, selection of roosting trees by the two Otus species may be shaped by predator avoidance, as birds select trees offering better camouflage and having spines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We could not measure the anti-predatory behaviour of owls in response to non-human predators. However, experimental results showed that flush response and flight initiation distance of roosting owls decreased in response to approaching human stimuli when they roosted in well concealed spiny vegetation (Sureshmarimuthu et al 2021). Our results suggest thus, that on Andaman Islands, selection of roosting trees by the two Otus species may be shaped by predator avoidance, as birds select trees offering better camouflage and having spines.…”
Section: Discussionmentioning
confidence: 99%
“…Among the five species of owls known to occur in Andaman Islands, Andaman Scops-owl Otus balli , endemic to the Andaman Islands, is associated with evergreen-dominated patches, while the Oriental Scops-owl O. sunia (subspecies modestus ) is more widespread and common throughout the Andaman Islands (Babu et al 2019). Both species were reported to prefer to roost on the limbs of tree foliage in Andaman (Sureshmarimuthu et al 2021). Since the lack of knowledge in the differential roost site requirements of these sympatric tropical owls and the ongoing threats on these Islands, in this study, we aimed to identify the factors that influence the summer roost site selection of the two sympatric Otus owl species through a multi-scale approach (at the roost tree, roost patch, and macro scales) in the mosaic habitats of the Andaman Islands.…”
Section: Introductionmentioning
confidence: 99%